Analytic Hierarchy Process as a Determinant of Irrigation Allocation Priorities with e-Paksi Parameters - Roliono, Cahyo Aji; Maulana, Mahendra Andiek; Savitri, Yang Ratri (Journal of Civil Engineering, 2025)
Optimal management of irrigation water allocation is an important challenge especially in areas with limited resources. The Analytical Hierarchy Process (AHP) method can be used as a tool in complex decision-making by considering various factors that affect water allocation. In this study, AHP is applied to address the gaps in the e-Paksi program that uses individual judgement, which applied a subjective norm values. This study seeks to achieve balanced water allocation priorities using that approach, reflecting the existing physical conditions and social interests of the community, as represented by the assessment of field practitioners. The criteria used in the AHP analysis include Physical Structure, Crop Productivity, Supporting Facilities, Organisation Personnel, Documentation, and Water User Farmers, derived from e-Paksi. The case study was conducted in the SIM Irrigation Area (D.I.), with secondary alternatives including Sumber Batang, Purwodadi, Ngabean, Bedilan, Karang, and Ulo. The results show that the highest irrigation allocation priority is given to Karang secondary with a priority value of 0.1735. The condition of Karang secondary based on UPI BBWS BS has an average value of 3.83 on a scale of 1 to 5. Integration of AHP approach with e-Paksi value criteria provides more comprehensive results for decision making in fair and appropriate irrigation water allocation.